PARADIGMA KOMUNIKASI ISLAM DALAM MENANGGULANGI TERORISME - Aisyah Khumairo (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2017)
Islamic communication is one of the most interesting themes to be discussed. Communication and terrorism are two terms that are often aligned by academics and practitioners. Terrorist acts become fluid not only because of the shrewdness of the perpetrators, but also because of intense communication among the various members to prepare all things. In tackling terrorism, Islamic communication that now has a lot of authority, must continue to be implemented properly. The paradigm used as a driver of Islamic communication should also be reviewed to adjust to the present conditions. Communication paradigm becomes important to be discussed because it is the framework of the implementation of Islamic communication in this contemporary era.